Nocardia xestospongiae sp. nov., isolated from a marine sponge in the Andaman Sea - Chitti Thawai; Nattawut Rungjindamai; Khanungkan Klanbut; Somboon Tanasupawat (My University, 2016)
A marine sponge-derived actinomycete, strain ST01-07T, was isolated from Xestospongia sp. collected from the Andaman Sea. The strain was characterised taxonomically using a polyphasic approach. The strain contained meso-diaminopimelic acid in the peptidoglycan, whole-cell sugars were arabinose, galactose, glucose, mannose and ribose. Mycolic acids that co-migrated with those from Nocardia araoensis NBRC 100135T were observed in whole-cell extracts. MK-8(H4ω-cycl) was the predominant menaquinone. Major cellular fatty acids were C17 : 1ω8c, C16 : 0 and C17 : 0. The diagnostic phospholipids in the cell consisted of diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylinositol. Phylogenetic analysis based on the 16S rRNA gene sequence showed that strain ST01-07T belonged to the genus Nocardia and was most closely related to N. araoensis IFM 0575T (98.71 % 16S rRNA gene sequence similarity), Nocardia niwae W9241T (98.56 %), Nocardia beijingensis AS4.1521T (98.41 %) and Nocardia arthritidis IFM 10035T (98.36 %). In addition, low DNA-DNA relatedness values (13.6±0.1% to 40.1±0.6%) confirmed that strain ST01-07T represents a novel species of the genus Nocardia, for which the name Nocardia xestospongiae sp. nov., is proposed. The type strain is ST01-07T (=BCC 45622T=NBRC 109069T).
Keywords: Diaminopimelic acid; Strain (injury); Arabinose; Nocardiaceae; Sponge; Genomics and Phylogenetic Studies